The last months of life of people with amyotrophic lateral sclerosis in mechanical invasive ventilation: A qualitative study. Issue 7 (December 2014) - Veronese, Simone; Valle, Alessandro; Chiò, Adriano; Calvo, Andrea; Oliver, David
Abstract In Italy 10–30% of patients who die with amyotrophic lateral sclerosis are invasively ventilated. It is difficult to predict when patients will die and when a specialist palliative care service may effectively be involved. Nineteen semi-structured interviews with informal family carers who looked after these patients who had died in last 10 years were undertaken to ascertain their experiences in the final stages of the disease. The mean survival after tracheostomy was 30 months (median 24 months). Fifty-eight percent of the patients had not wanted to be tracheostomized before the procedure, but often felt pressured into the decision to have a tracheostomy. Following the procedure the individual quality of life decreased for many patients and carers. In last 4–6 months both carers and patients were aware of a clear deterioration and reported cognitive-communication impairment, local infections and sepsis, pressure sores, the need for indwelling catheters and the use of sedative-analgesic drugs. The study shows that tracheostomy is often undertaken with little discussion. The end-of-life phase can be defined, with several indicators of deterioration, which could be triggers for the involvement of palliative care.